Iterated Boolean Sums of Bernstein Type Operators. (9th September 2020) - Acar, Tuncer; Aral, Ali; Raşa, Ioan
Abstract: The approximation of functions using linear positive operators is affected by saturation. The quality of approximation offered by iterated Boolean sums increases with the regularity of the function. We present some qualitative and quantitative results concerning the approximation by such Boolean sums. The general results are illustrated by examples.